The Integrative Model (STEM) and its effect on the achievements of mathematics (Journal of the College of Basic Education, 2019)
The current research aimed to identify the impact of the integrative model (STEM) in the collection of mathematics and skills Mathematical interdependence In the first grade students, the experimental method was adopted in the two groups (experimental and control) with a post-test. The number of members of the research sample was (62) students of the first intermediate grade divided into two groups, According to the integrated model STEM and another officer, the number of its members (30) students studied according to the usual method, and the equality of the two groups a number of variables. The achievement test was conducted in mathematics and in the six levels of the Bloom classification (knowledge, comprehension, application, analysis, composition, evaluation) of 30 experimental paragraphs. The results showed that the experimental group studied using the STEM model was superior to the control group studied according to the normal method. It was recommended that in-service mathematics teacher training programs be included in the use of the STEM teaching in middle schools.